Culeolus antarcticus Vinogradova 1962 - Sanamyan, K. E.; Sanamyan, N. P. (Zenodo, 2002)
Culeolus antarcticus Vinogradova, 1962 (®gure 24) Culeolus antarcticus Vinogradova, 1962b: 207; Monniot and Monniot, 1982: 117; 1985b: 31. Culeolus sluiteri : Diehl, 1977: 147. Material examined . St. 896, 5651±5530 m, one specimen; st. 925, 2980±2960 m, one specimen; st. 908, 5474±5465 m, one specimen; st. 916, 4664±5631 m, ®ve specimens. Description . The body length is from 10 to 36 mm and all the specimens have broken peduncles. The general body shape is similar in all specimens, the body being elongate and slightly tapering anteriorly. The thin and ®rm test is completely covered by small spherules. A few of these slightly protrude like small papillae, but in a 30 mm specimen from st. 925, the papillae are longer and more numerous, giving the specimen a shaggy appearance. The postero-ventral crest is T-shaped (®gure 24A), it consists of a short mid-ventral branch and two lateral branches running obliquely from the most postero-ventral point of the body and ending some distance from the corners of the slit-like atrial aperture. The lateral branches are straight or their free ends slightly curved dorsally and posteriorly (but not ventrally as ®gured by Vinogradova, 1962b). The mid-ventral branch is absent only in the smallest (10 mm) specimen. The postero-ventral crest has sometimes free papillae, or they are united along most of their length to form a solid lamella. Papillae are arranged in one line in most specimens, but are crowded and form a wide band in the`shaggy’ specimen referred above. About 22 large and heavily branched tentacles are present. In opened specimens they hide the whole prebranchial area and project beyond the rim of the branchial siphon. The branchial sac has usually six folds on each side, but only ®ve on the right side in the 30 mm specimen from st. 908. The branchial formula of the ®gured specimen is: E2(3)2(4)2 (6)4 (7)3(7)4 (4)2DL3(5)5 (4)3(6)3(5)2 (3)1(4)2E. One gonad is present on each side of the body, the left is in the gut loop. Each gonad consists of three to seven lobes; the number of lobes does not necessarily depend on body size as the two smallest specimens (10 and 15 mm long) have seven lobes on the left gonad and three on the right, but the 30 mm specimen has ®ve and four lobes, respectively. The anal border is characteristic, with two ¯at lobes, each with a lobed rim. Remarks . Although the postero-ventral crest may be solid or formed by papillae of various lengths, its general shape is constant and this is a good distinguishing character for the species. On the other hand, the presence or absence of other papillae on the body is variable. The presence of only one, usually long, gonad on each side of the body, and the shape of the anal border are other distinguishing characters. The species was initially described from the Indian sector of the Antarctic and then recorded from the south-east Paci®c and the south-west Atlantic, the Ross Sea; the most northern record is from the Cape Basin (33 ss N). It probably has a periantarcti c distribution. This is the deepest record for this species, the greatest depth previously recorded was 4820 m. : Published as part of Sanamyan, K. E. & Sanamyan, N. P., 2002, Deep-water ascidians from the south-western Atlantic (RV Dmitry Mendeleev, cruise 43 and Academic Kurchatov, cruise 11), pp. 305-359 in Journal of Natural History 36 (3) on pages 342-344, DOI: 10.1080/00222930010004232, http://zenodo.org/record/5299679 : {"references": ["VINOGRADOVA, N. G., 1962 b, Ascidiae simplices of the Indian part of the Antarctic, in Explorations of the Fauna of the Seas, 1 (9). Biological Results of the Soviet Antarctic Expedition (1955 \u00b1 1958), 1, 196 \u00b1 215 (in Russian).", "MONNIOT, C. and MONNIOT, F., 1982, Some antarctic deep-sea tunicates in the Smithsonian collections, Antarctic Research Series, 32, 95 \u00b1 130.", "MONNIOT, C. and MONNIOT, F., 1985 b, Nouvelles reAcoltes de Tuniciers benthiques profonds dans l'oceAan Atlantique, Bulletin du MuseAum national d'Histoire naturelle, Paris, (4), 7 A, 5 \u00b1 37.", "DIEHL, M., 1977, Ascidien des Argentinischen Schelfs aus den Grundtrawl-FaEngen des FFS`Walter Herwing' auf seiner dritten SuEdamerika-Expedition, Mitteilungen aus dem zoologischen Museum Hamburg, 74, 139 \u00b1 153.", "MICHAELSEN, W., 1904, Die Stolidobranchiaten Ascidien der deutschen Tiefsee Expedition, Wissenschaftlichen Ergebnisse der Deutschen Tiefsee-Expedition, 7, 181 \u00b1 260."]}